2019
DOI: 10.1177/1060028019838239
|View full text |Cite
|
Sign up to set email alerts
|

Sound-Alike Look-Alike Confusion and Matching Medication Product Attributes: Simulated Case-Control Studies

Abstract: Background: Sound-alike look-alike (SALA) medication confusions harm as many as 250 000 Americans annually. Most preventive strategies focus on medication name similarities. Objectives: To evaluate the association between matching medication product attributes and SALA confusion. Methods: We simulated 20 000 case-control studies using the Institute for Safe Medication Practices’ List of Confused Drug Names as case pairs and 4 randomly selected control pairs per case pair from the First DataBank MedKnowledge (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Recent studies have reported that incorrect identification of look-alike tablets or pills figures prominently amongst fears surrounding medication errors, 10 while "soundalike look-alike" medication confusions harm as many as a quarter of a million of Americans annually. 11 The development of MIND into a smartphone application coupled with a portable spectrometer may be useful for a variety of health professionals wishing to identify medicines. The content of the MIND databases requires continuous updating to include new medicines, and to modify existing medicines for any changes of the solid oral form.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that incorrect identification of look-alike tablets or pills figures prominently amongst fears surrounding medication errors, 10 while "soundalike look-alike" medication confusions harm as many as a quarter of a million of Americans annually. 11 The development of MIND into a smartphone application coupled with a portable spectrometer may be useful for a variety of health professionals wishing to identify medicines. The content of the MIND databases requires continuous updating to include new medicines, and to modify existing medicines for any changes of the solid oral form.…”
Section: Discussionmentioning
confidence: 99%
“…More recent research into predictors of confusable medicine pairs by Her and Toh confirmed that similarity in product characteristics, particularly between medicines from the same manufacturer, are significant. 3 Our premise is that these factors may be considered by clinical experts alongside practice-related risks such as the proximity of storage of the LASA medicines and their use in high-pressure clinical environments. As such, the computational outputs require interpretation in relation to the clinical setting and the respective presentations of the confused medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Risks associated with confusable medicine names have been recognized in the literature [1][2][3][4] and the emergence of quality and safety initiatives in the past decade. Medicine names that look alike and/or sound alike (LASA) require vigilance during their prescribing, dispensing, administration to patients and monitoring, 1 and across manual and electronic processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation